Book Notes [65, Spring 2010] - Finkel, Alvin (Labour/Le Travail, 2010)
The article briefly reviews "Up in the Air," by Greg J. Bamber, Jody Hoffer Gittell, Thomas A. Kochan, and Andrew von Nordenflycht, "To Be My Father's Daughter," by Sharon Halfyard, Carmelita McGrath, and Marion Cheeks, "The Welfare State Nobody Knows: Debunking Myths About U.S. Social Policy," by Christopher Howard, "In and Out of the Working Class," by Michael D. Yates, "Icon, Brand, Myth: The Calgary Stampede," edited by Max Foran, "From Hands Now Striving to Be Free: Boxes Crafted by 1837 Rebellion Prisoners," by Chris Raible with John C. Carter, "Reshaping Welfare States and Activation Regimes in Europe," by Amparo Serrano Pascual and Lars Magnusson, "Impossible Peace: Israel/Palestine Since 1989," by Mark LeVine, "Pathologies of Power: Health, Human Rights and the New War on the Poor," by Paul Farmer, "Why Not Socialism?," by G.A. Cohen, and "More Unequal," edited by Michael D. Yates.